55.7k views
0 votes
12x−39≤9 AND−4x+3<−6

User Ajeanson
by
5.6k points

2 Answers

4 votes

Answer:

2.25<x≤4

Explanation:

12x−39≤9 ⇒ 12x≤ 48 ⇒ x≤4

−4x+3<−6 ⇒ -4x < -9 ⇒ x> 9/4= 2.25

2.25<x≤4

or

x= (2.25, 4]

User InnisBrendan
by
5.2k points
6 votes

Answer:

2 1/4 < x ≤ 4

Explanation:

12x−39≤9 AND−4x+3<−6

Solve them separately and then put back together

12x−39≤9

Add 39 to each side

12x−39+39≤9+39

12x ≤48

Divide by 12

12x/12 ≤48/12

x ≤4

Now the other inequality

−4x+3<−6

Subtract 3 from each side

−4x+3-3<−6-3

-4x < -9

Divide by -4, remembering to flip the inequality

-4x/-4 > -9/-4

x > 2 1/4

put back together

x > 2 1/4 and x ≤4

2 1/4 < x ≤ 4

User Tezzo
by
6.1k points